Saliva urea nitrogen dipsticks to predict acute kidney injury in Malawian trauma patients - Bjornstad, Erica; Muronya, William; Smith, Zachary H; Kamija, Manly; Evans, Rhys; Mottl, Amy K; Golightly, Yvonne M; Gibson, Keisha; Charles, Anthony; Gower, Emily W (African Journal of Nephrology, 2023)
Background: Many low-resource settings have limited access to serum creatinine tests necessary for kidney disease identification. Among Malawian patients who are hospitalized after trauma, we evaluated the use of point-of-care saliva urea nitrogen (SUN) dipsticks to predict acute kidney injury (AKI). Methods: In a nested prospective cohort study, we enrolled hospitalized acute trauma patients aged ≥6 months to evaluate AKI (defined by KDIGO criteria) and the test characteristics of SUN to predict AKI. Results: Among 335 participants (approximately three-quarters able to expectorate and 34% aged ≤18 years), 12.5% (n = 42) developed AKI. At a SUN threshold of ≥40 mg/dL, a positive dipstick test was specific (99.3%) but insensitive (14.3%) in predicting AKI, with a positive predictive value of 75% and negative predictive value of 89%. At this threshold, 2.4% of participants were dipstick-positive (SUN+), and 75% of those had AKI. Reducing the SUN threshold to ≥30 mg/dL increased participants who were SUN+ to 5.0% (n = 16) but also increased the false positive rate and missed 79% (n = 33) of AKI cases. Stratified results showed better performance among adults than children and similar results when comparing participants who could and could not expectorate. There was moderate correlation between categorized BUN values and SUN (r = 0.53) but less agreement (weighted kappa 0.27; 95% CI 0.17–0.37). Conclusions: SUN dipstick testing has good specificity and negative predictive value for ruling out AKI, but poor sensitivity. We found similar results among those who could or could not expectorate a saliva sample.